2007
DOI: 10.1111/j.1553-2712.2007.tb02015.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Dextrose during Outpatient Rehydration in Pediatric Gastroenteritis

Abstract: Background: Rapid intravenous (IV) rehydration in the emergency department (ED) is required for certain children with acute gastroenteritis (AGE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Nevertheless, we probably enrolled some children with mild dehydration. The inclusion of this group enhances the pragmatic nature of this trial as our study population is similar to those included in other intravenous rehydration studies in developed countries,41 42 43 44 and hence are candidates for rapid intravenous rehydration. Furthermore, subgroup analysis did not show a trend towards increased benefit in children with more severe dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we probably enrolled some children with mild dehydration. The inclusion of this group enhances the pragmatic nature of this trial as our study population is similar to those included in other intravenous rehydration studies in developed countries,41 42 43 44 and hence are candidates for rapid intravenous rehydration. Furthermore, subgroup analysis did not show a trend towards increased benefit in children with more severe dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…47 It has also been demonstrated that the rate of re-presentation admissions is significantly lower in children who have glucose administered on their first presentation with gastroenteritis, independent of the volume of fluid administered. 48 These outcomes are unlikely to be because of glucose causing an improvement in hydration, but because of an effect on improving acid-base state by reversing ketosis. Further research to examine this relationship in a larger cohort is warranted.…”
Section: Box 2 Case 2: Ketoacidosis Without Hypoglycaemiamentioning
confidence: 99%